Inhibition of HDAC6 activity in kidney diseases: a new perspective - Ben Ke; Yanxia Chen; Wei Tu; Ting Ye; Xiangdong Fang; Liping Yang (BMC, 2018)
Abstract Histone deacetylase 6 (HDAC6), a cytoplasmic enzyme that plays important roles in many biological processes, is one isoform of a family of HDAC enzymes that catalyse the removal of functional acetyl groups from proteins. HDAC6 stands out from the other members of this family because it almost exclusively deacetylates cytoplasmic proteins and exerts deacetylation-independent effects, which has led to the successful development of relatively isoform-specific inhibitors of its enzymatic action. Numerous studies have recently demonstrated that HDAC6 expression and activity are increased in kidney disease, such as autosomal dominant polycystic kidney disease (ADPKD), renal fibrosis, and acute kidney injury (AKI), among others. Moreover, HDAC6 inhibitors have been investigated for use in treating these diseases. In fact, HDAC6 inhibitors effectively limit the progression of kidney diseases, suggesting that targeting HDAC6 may provide a novel treatment approach. However, the primary challenge in developing HDAC6-targeted therapies is understanding how the renoprotective effect of NDAC6 inhibitors can be selectively harnessed. Here, we discuss the unique function of HDAC6 and recapitulate the alluring potential of its inhibitors in kidney diseases.